Pemanfaatan Media Digital dalam Komunikasi Organisasi Penyelenggaraan Ibadah Haji di Sumatera Utara - Siregar, Alya Rahmayani; Syukur Kholil (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to explore the benefits of using digital media in the context of organizational communication organizing the Hajj pilgrimage in North Sumatra. The focus of the research is on analyzing the role of digital media in various aspects of organizing the Hajj pilgrimage as well as evaluating the level of satisfaction felt by various related parties, such as prospective Hajj pilgrims, pilgrim families, organizing organizations and government stakeholders. The research method applied is a qualitative approach with data collection techniques through in-depth interviews, participatory observation and documentation studies. The collected data was analyzed thematically by coding and categorizing to identify main patterns and themes. The research results show that digital media has a significant role in disseminating information, internal coordination, training and guidance, service and support, as well as documentation and archives related to the implementation of the Hajj pilgrimage in North Sumatra. The use of digital media provides satisfaction for various parties by providing easy access to information, monitoring worship trips, efficient communication and coordination, as well as transparency and accountability. However, this level of satisfaction is influenced by factors such as accessibility, content quality, and ease of use of digital media. Therefore, this research provides recommendations for improving the quality and effectiveness of the use of digital media in organizational communications organizing the Hajj pilgrimage in North Sumatra.